Plínio Marcosy Juan Radrigan: Íconos del teatro de resistencia - Alexandre, Marcos Antônio; Rojo, Sara (Latin American Theatre Review, 2007)
This article shows how, in the darkest period of Latin America (the period of military dictatorships), there was an increased focus on activity critical of the system. It is within that framework of resistance and rupture that the works of Brazilian Plinio Marcos (1936-1999) and the Chilean Juan Radrigan (1937), which we are calling hyperrealist, were born. Through their actions, the characters within the dramatic worlds of Radrigan and Plinio Marcos show us, by analogy, not their personal histories, but rather the history of their people in a particular context, specifically a sector of their societies that generally is not valued by those who uphold power or even by those who are successfully located inside the system. (MAA/SR, in Spanish)